Socio-Onomastics Analysis on Aristocratic Names in South Nias - Laia, Yonatan Eklesia; Umiyati, Mirsa; Muliana, I Nyoman (CV Wahana Publikasi, 2025)
The aristocratic names in South Nias differ from the proper names generally. Instead, it used common nouns to describe name bearers, which are influenced by the language, social, and cultural factors of South Nias. This research was conducted in Öri Maniamölö, South Nias, focusing on four sample villages as members of a group of villages in Öri Maniamölö: Bawömataluo, Hilinawaö Fau, Botohilitanö, and Hilisimaetanö villages. The results of the analysis revealed that aristocratic names in South Nias have meanings categorized into social stratification, natural aspects, instruments and tools, specific names, and human activity. Additionally, there were four functions of aristocratic names in South Nias: as the identifier of someone’s greatness and majesty, as the authority sign of the name bearer, as an identifier of family ancestry, and as the representative of the name bearer’s characteristics. Linguistically, there are four morphological processes in word formation in the data obtained, namely: 1) Prefixation which consisted of sa-, s(i)-, so-, na-, ni-, da-, fa-, ma-, mo-, me-,i-, te-/to-. Then, 2) Circumfix, which consists of one data, namely a-ta, with the role of changing verbs into nouns. Next, 3) Suffixation, which consists of the suffix -ma, which functions as a nominalizer. The last process is 4) Reduplication that occurs in the words ‘Daro-daro’ by repeating the same word and still in the same word class as noun.